2017
DOI: 10.4162/nrp.2017.11.5.365
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ingredients of Korean brown rice cookies on attenuation of cholesterol level and oxidative stress in high-fat diet-fed mice

Abstract: BACKGROUND/OBJECTIVESOwing to health concerns related to the consumption of traditional snacks high in sugars and fats, much effort has been made to develop functional snacks with low calorie content. In this study, a new recipe for Korean rice cookie, dasik, was developed and its antioxidative, lipid-lowering, and anti-inflammatory effects and related mechanisms were elucidated. The effects were compared with those of traditional rice cake dasik (RCD), the lipid-lowering effect of which is greater than that o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…In our previous studies, our team has observed lipid-lowering effects of the RC in high fat fed mice compared with the western style cookie [12]. In addition, GBRC demonstrated greater lipid lowering effects relative to the RC [19]. The ingredients of RC are 55.6% rice cake flour, 22.2% mung bean starch, and 22.2% honey.…”
Section: Sample Selection and Preparation Of Experimental Dietsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous studies, our team has observed lipid-lowering effects of the RC in high fat fed mice compared with the western style cookie [12]. In addition, GBRC demonstrated greater lipid lowering effects relative to the RC [19]. The ingredients of RC are 55.6% rice cake flour, 22.2% mung bean starch, and 22.2% honey.…”
Section: Sample Selection and Preparation Of Experimental Dietsmentioning
confidence: 99%
“…The ingredients of RC are 55.6% rice cake flour, 22.2% mung bean starch, and 22.2% honey. GBRC, developed functional dasik cookie, is composed of 75.6% brown rice flour, 22.0% FOS, 2.3% red ginseng extract, and 0.06% propolis [19]. The calories of RC and GBRC are 347.9 and 344.9 kcal per 100 g of cookie, respectively.…”
Section: Sample Selection and Preparation Of Experimental Dietsmentioning
confidence: 99%
“…ese immune cells further stimulate the production of ROS by activating several enzymes such as NADPH oxidase and xanthine oxidase. Excessive ROS induce oxidative damage of DNA, lipids, and proteins in cells, thereby leading to various diseases [4,5].…”
Section: Introductionmentioning
confidence: 99%